2023
DOI: 10.1002/adma.202308332
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic All‐Solid‐State Sodium Batteries: Electrolyte Designing and Interface Engineering

Yaxiong Yang,
Shoumeng Yang,
Xu Xue
et al.

Abstract: Inorganic all‐solid‐state sodium batteries (IASSSBs) are emerged as promising candidates to replace commercial lithium‐ion batteries in large‐scale energy storage systems due to their potential advantages, such as abundant raw materials, robust safety, low price, high‐energy density, favorable reliability and stability. Inorganic sodium solid electrolytes (ISSEs) are an indispensable component of IASSSBs, gaining significant attention. Herein, this review begins by discussing the fundamentals of ISSEs, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 278 publications
0
7
0
Order By: Relevance
“…Strikingly, the calculated activation energy of Na diffusion in A-phase Na 7 TaP 4 is only 0.24 eV using ML-MD simulations, which is among the lowest known values for Na-ion SSEs. 7,76–78 This result manifests that crystal structure engineering has a significant impact on the Na diffusion properties. As this is the key finding of this work, we paid substantial efforts to check its accuracy by performing all-DFT MD simulations.…”
Section: Resultsmentioning
confidence: 76%
“…Strikingly, the calculated activation energy of Na diffusion in A-phase Na 7 TaP 4 is only 0.24 eV using ML-MD simulations, which is among the lowest known values for Na-ion SSEs. 7,76–78 This result manifests that crystal structure engineering has a significant impact on the Na diffusion properties. As this is the key finding of this work, we paid substantial efforts to check its accuracy by performing all-DFT MD simulations.…”
Section: Resultsmentioning
confidence: 76%
“…21 Although ceramic electrolytes have certain advantages (electrochemical stability, Li + conductivity, and mechanical strength), their brittle nature, high electrolyte−electrode interfacial resistance, and high processing costs limit their commercial applications. 22 SPEs are a combination of polymers, e.g., poly(ethylene oxide) (PEO), polyvinylidene fluoride (PVDF), poly(vinyl alcohol) (PVA), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), poly(methyl methacrylate) (PMMA), poly(vinylpyrrolidone) (PVP), etc., and different Li-salts (LiTFSI, LiFSI, LiClO 4 ). 23,24 SPEs generally exhibit flexibility and good interfacial contact with the electrodes and can accommodate the volumetric expansion of electrodes during the charge−discharge cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the substitution of Y 3+ at the Zr-site in LZP stabilizes the rhombohedral structure in the Li 1.15 Y 0.15 Zr 1.85 (PO 4 ) 3 phase with a total Li-ion conductivity of ∼3.5 × 10 –5 S cm –1 . Although ceramic electrolytes have certain advantages (electrochemical stability, Li + conductivity, and mechanical strength), their brittle nature, high electrolyte–electrode interfacial resistance, and high processing costs limit their commercial applications …”
Section: Introductionmentioning
confidence: 99%
“…Achieving global carbon neutrality hinges on the continual advancement and widespread implementation of large-scale energy storage systems (ESSs). Lithium-ion batteries (LIBs), as one of the earliest commercialized ESSs, have already changed our life by their applications in electric vehicles and mobile electronics. However, due to the shortage of lithium resources and the rising price of lithium salts, sodium-ion batteries (SIBs) present broad market prospects as the alternatives to complement LIBs in sustainable energy storage devices. Besides, the physicochemical affinities between lithium and sodium afford the development of SIBs by drawing upon the extensive and successful research foundations established for LIBs. Given the cathode material’s significant influence on a battery’s cost and its electrochemical attributessuch as cycle stability, rate capability, and energy densitythe exploration of suitable cathode materials for SIBs becomes paramount. The investigation of cathode materials for SIBs mainly includes primarily transition metal oxides, polyanion compounds, , and Prussian blue analogues. , Statistics over the past five years reveal a consistent annual growth in papers related to these cathode materials as shown in Figure a, and the volume of articles on layered transition metal oxide (LTMO) cathode materials surpasses that of the other two cathode materials.…”
Section: Introductionmentioning
confidence: 99%